1976
DOI: 10.1021/ja00424a073
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of positron lifetimes in carbonic anhydrase

Abstract: references cited therein; (d) H. Basch, Theor. Chim. Acta, 28, 151 (1973). We thank Professor C. Trindle (University of Virginia) for this reference.(3) For reviews, see (a) G. L. Closs in Top. Stereochem., 3, 193 (1968); (b) P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1977
1977
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 1 publication
0
7
0
Order By: Relevance
“…However, he focused his attention on the order and arrangement of tissue water and not on muscle structure. Further studies on complex biological systems like biological membranes or proteins moved positronium research towards structural biology and showed that this approach was efficient in the study of biological reactions (such as electron transfer (Jean and Ache, 1977)), phase transition of lipids (Chow et al, 1981;Jean and Hancock, 1982;Stinson et al, 1980) macromolecule structure (Handel et al, 1976), hydratation (Akiyama et al, 2007Gregory et al, 1992;Handel et al, 1980) and porosity (Chamerski et al, 2017;Pamula et al, 2006) of biological samples. Nowadays, after many years of focused research, PALS appears to be a promising technique in the investigation of the structure of macromolecules (Chen et al, 2012) and clinical samples (Avachat et al, 2022;Moskal et al, 2021a,b;Zgardzinska et al, 2020).…”
Section: Development Of Positronium Research In Biology and Medicinementioning
confidence: 99%
See 2 more Smart Citations
“…However, he focused his attention on the order and arrangement of tissue water and not on muscle structure. Further studies on complex biological systems like biological membranes or proteins moved positronium research towards structural biology and showed that this approach was efficient in the study of biological reactions (such as electron transfer (Jean and Ache, 1977)), phase transition of lipids (Chow et al, 1981;Jean and Hancock, 1982;Stinson et al, 1980) macromolecule structure (Handel et al, 1976), hydratation (Akiyama et al, 2007Gregory et al, 1992;Handel et al, 1980) and porosity (Chamerski et al, 2017;Pamula et al, 2006) of biological samples. Nowadays, after many years of focused research, PALS appears to be a promising technique in the investigation of the structure of macromolecules (Chen et al, 2012) and clinical samples (Avachat et al, 2022;Moskal et al, 2021a,b;Zgardzinska et al, 2020).…”
Section: Development Of Positronium Research In Biology and Medicinementioning
confidence: 99%
“…The first applications of positronium properties in the life sciences were made by Handel in late 70s (Handel et al, 1976(Handel et al, , 1980. Having in mind that positron annihilation lifetime is sensitive to changes in free volume caused by pressure (which is rarely studied in biological systems) or by thermal expansion in the same phase, he showed significant changes in positronium lifetime during phase transitions of biological systems.…”
Section: A Positronium In Biological Materials and Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…The application of the positron annihilation technique to biophysical problems is rather recent (cf. Handel et al, 1976;McMahon et al, 1979;Graf et al, 1979). Here we investigate our suggestion that the positron is a sensitive probe of protein conformation.…”
Section: Introductionmentioning
confidence: 99%
“…The fivecoordinate halogenobis(diethyldithiocarbamato) iron (III) complexes, which are paramagnetic and hardly reducible, were also tested for the effect on the o-Ps quenching. Unlike the six-coordinate iron(III) dithiocarbamates, they only slightly affected the o-Ps lifetime, indicating that the spin-conversion process of o-Ps quenching is much less important than the oxidation process.Positronium, which is the bound state of a positron with an electron, has attracted increasing attention from many researchers and the positron annihilation as a nuclear probe has been widely applied to the study of the chemical [ 1 -6 ], miceller [ 7 -9 ], and biological systems [10][11][12]. The variation of the intensity of the long-lived component of positronium against the inhibitor concentration in systems of organic solutions has recently been successfully explained in terms of the spur model [13][14][15].…”
mentioning
confidence: 99%